INDIKASI VITREKTOMI PADA KELAINAN RETINA DI BALAI KESEHATAN MATA MASYARAKAT (BKMM) PROPINSI SULAWESI UTARA PERIODE JANUARI 2014-DESEMBER 2014 - Sinaga, Rohamonangan Theresia; Rares, Laya; Sumual, Vera (e-CliniC, 2016)
Abstract: The prevalence of retinal abnormality in Indonesia reached 0.13% and is the fourth leading cause of blindness after cataract, glaucoma. and refractive disorders. Vitrectomy is a type of surgery to treat retinal disorders that removes the vitreous, therefore, the operation can be performed and vision can be corrected. This study aimed to determine the indications to undergo vitrectomy in retinal disorders. This was a descriptive retrospective study using data of medical records of patients with retinal disorders who underwent vitrectomy at Community Eye Health Center (CEHC) of North Sulawesi Province. There were 27 patients in this study consisted of 17 male patients (63%) and 10 female patients (37%). The major indications of vitrectomy were retinal detachment in 16 patients (59%) and diabetic retinopathy in 11 patients (41%). In case of retinal detachment male patients were the most frequent to undergo vitrectomy (12 patients; 44.44%) than female patients (4 patients; 14.81%). In case of diabetic retinopathy there were no difference between males (18.52%) and females (22.22%)Keywords: retinal disorder, vitrectomy, retinal detachment, diabetic retinopathy Â Abstrak: Prevalensi kelainan retina di Indonesia mencapai 0,13% dan merupakan penyebab kebutaan keempat setelah katarak, glaucoma, dan kelainan refraksi. Vitrektomi adalah salah satu jenis operasi untuk mengobati kelainan retina melalui pengangkatan vitreus sehingga retina dapat dioperasi dan penglihatan dapat diperbaiki. Penelitian ini bertujuan untuk mengetahui indikasi dilakukannya vitrektomi pada kelainan retina. Jenis penelitian ini deskriptif retrospektif dengan menggunakan data dari rekam medis penderita dengan kelainan retina yang menjalani vitrektomi di Balai Kesehatan Mata Masyarakat (BKMM) Propinsi Sulawesi Utara. Dalam penelitian ini ditemukan 27 pasien dengan kelainan retina yang menjalani vitrektomi terdiri dari 17 pasien laki-laki (63%) dan 10 pasien perempuan (37%). Indikasi untuk vitrektomi terbanyak pada retinal detachment sebanyak 16 pasien (59%) dan retinopati diabetik sebanyak 11 pasien (41%). Pada indikasi retinal detachment didapatkan pasien laki-laki yang paling banyak menjalani vitrektomi yaitu 12 pasien (44,44%) sedangkan perempuan 4 pasien (14,81%). Pada indikasi retinopati diabetik tidak terdapat perbedaan antara laki-laki (18,52%) dan perempuan (22,22%)Kata kunci: kelainan retina, vitrektomi, retinal detachment, retinopati diabetik